"Everyone needs a class like this": High school students' perspectives on a gay and lesbian literature course - Helmer, Kirsten (Educational Forum, 2015)
This article offers insights on how students experienced and made sense of their learning in a trimester-long high school Gay and Lesbian Literature course. Drawing on questionnaires and interviews that the students completed as part of a larger ethnographic study of this class, the author shows how a queer-themed literature curriculum is relevant for both LGBTQ-identifying and straight-identifying students and contributes to a better school climate.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; identités LGBTQIA2+; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science de l'éducation; thématiques; école secondaire; états-unis

Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques